Efficacy of Intrathecal Fentanyl for Cesarean Delivery: A Systematic Review and Meta-analysis of Randomized Controlled Trials With Trial Sequential Analysis. Issue 2 (June 2020) - Uppal,; Retter, S.; Casey, M.; Sancheti, S.; Matheson, K.; McKeen, D.M.
Abstract : ( Anesth Analg . 2020;130:111–125) Cesarean delivery procedures have become more popular over the past few decades, and spinal anesthesia is a commonly used method of anesthesia for that operation. A majority of surveyed members of the Society for Obstetric Anesthesia and Perinatology stated that they preferred to administer hyperbaric 0.75% bupivacaine spinal anesthesia for cesarean deliveries, while a smaller percentage of anesthesiologists reported adding fentanyl, morphine, or a combination of both to an intrathecal bupivacaine solution. The addition of intrathecal opioids to spinal anesthesia medication has been reported to be effective for pain relief in some cases, but researchers are still unsure of the benefits, drawbacks, and optimal dosages of these medications. These investigators conducted their systematic review and meta-anlaysis to analyze the effectiveness of fentanyl both alone and in combination with morphine when added to intrathecal bupivacaine anesthesia during a cesarean delivery.